2020
DOI: 10.1101/2020.03.31.20049122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Globalized low-income countries may experience higher COVID-19 mortality rates

Abstract: Understanding the factors underpinning COVID-19 infection and mortality rates is essential in order to implement actions that help mitigate the current pandemic. Here we evaluate how a suit of 15 climatic and socio-economic variables influence COVID-19 exponential growth-phase infection and mortality rates across 36 countries. We found that imports of goods and services, international tourism and the number of published scientific papers are good predictors of COVID-19 infection rates, indicating that more glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…The role of environmental drivers on COVID-19 spatial patterns and growth rate is controversial (Araújo et al, 2020; Carlson et al, 2020a; Carlson et al, 2020b; National Academies of Sciences Engineering and Medicine, 2020). Some authors suggested that this disease had a reduced impact and spread in warm climates, and in areas with low pollution and experiencing intense UV radiation (Merow and Urban, 2020; Rahman et al, 2020; Runkle et al, 2020; Sajadi et al, 2020; Sobral et al, 2020; Wu et al, 2020b; Wu et al, 2020c; Zhang et al, 2020), while others reported that socio-economic factors and airport connections have a much stronger impact than environmental drivers (Coelho et al, 2020; Jaffe et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of environmental drivers on COVID-19 spatial patterns and growth rate is controversial (Araújo et al, 2020; Carlson et al, 2020a; Carlson et al, 2020b; National Academies of Sciences Engineering and Medicine, 2020). Some authors suggested that this disease had a reduced impact and spread in warm climates, and in areas with low pollution and experiencing intense UV radiation (Merow and Urban, 2020; Rahman et al, 2020; Runkle et al, 2020; Sajadi et al, 2020; Sobral et al, 2020; Wu et al, 2020b; Wu et al, 2020c; Zhang et al, 2020), while others reported that socio-economic factors and airport connections have a much stronger impact than environmental drivers (Coelho et al, 2020; Jaffe et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The huge variation of COVID-19 growth rates among regions with similar climate and air quality levels highlights that diverse and complex social and demographic factors, as well as stochasticity, may strongly contribute to the severity of local outbreaks, irrespective of environmental effects. The potential socio-economic drivers of COVID-19 outbreak are many (Coelho et al, 2020; Jaffe et al, 2020). Even if we did not manage to model the spatial spread of the disease across regions, we integrated several variables reflecting potential socio-economic drivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we observe the same pattern at country level. Faster spread in regions with larger populations have been explained by the interaction of frequent trades and people exchanges, and the difficulty to control early outbreaks within larger populations (Jaffe, Vera & Jaffe, 2020;Harbert, Cunningham & Tessler, 2020;Stier, Berman & Bettencourt, 2020). Because of the multiple infection routes and faster spread in larger populations, recent discussions emphasize the need to implement more aggressive social distancing policies in regions with larger populations (Stier, Berman & Bettencourt, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed the same pattern at country level. Faster spread in regions with larger populations have been explained by the interaction of frequent trades and people exchanges, and the difficulty to control early outbreaks within larger populations (Jaffe et al 2020, Harbert et al 2020, Stier et al 2020).…”
Section: Discussionmentioning
confidence: 99%